Recycling of Organic Wastes through the Vermicomposting Process of Cow Dung and Crop Residues (Journal of Bangladesh Academy of Sciences, 2018)
Fertilizer is considered to be one of the main inputs for increasing crop yields. Chemical fertilizer industries are highly energy intensive and have a fundamental dependence on natural gas supply. On the other hand, organic fertilizers are the safer sources of plant nutrients without any detrimental effect on crops and soil. In the era of technological innovation, the farmers are interested to grow HYV rice and other diversified crops to support huge population of Bangladesh. So various harmful chemicals were used which degraded the health of the soil. Vermicompost is an excellent, nutrient-rich organic fertilizer and soil conditioner. It can bring back the fertility of the soil. Vermicomposting with earthworms has been recognized as a composting technique that transforms complex organic substances into stabilized, humus-like product. The application of vermicompost to the soil is considered as a good management practice in any agricultural production system because of the stimulation of soil microbial growth and activity and mineralization of plant nutrients and increased soil fertility and quality. This research focuses on producing nutrient-rich organic fertilizer by vermicomposting process from biomass. An experimental setup was carried out in Doulatpur, Kushtia targeting 10 tons output per month. Cow dung and crop residues were collected and followed vermicomposting method. Three cycles were maintained in the experiments i.e. 120 days per cycle-360 days in total and counted the vermi population for each consecutive cycle. The output fertilizer was analyzed in the laboratory and it was observed that the component ratios were suitable for agricultural lands. This fertilizer can also be used as a remedy for the barren lands. For the sustainable crop production and net improvement of soil productivity, vermicomposing is an excellent process to produce organic fertilizer from biomass.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 1-9, 2018